2013
DOI: 10.1177/1753193412475241
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perspective of wide-awake hand surgery — 100 consecutive cases

Abstract: The wide-awake hand surgery (WAHS) technique involves injecting lidocaine with adrenaline for hand surgical procedures that are done without the use of tourniquets, sedation, regional or general anaesthetic. This is a retrospective review of the first 100 consecutive patients who underwent operations using this technique at our centre. The operations included carpal and cubital tunnel decompression, trapeziectomy, tendon transfer, and tenolysis. A questionnaire adapted from Lalonde's previous work on wide-awak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 25 publications
8
48
0
1
Order By: Relevance
“…Ninety-one percent of their patients felt the pain they experienced during surgery was comparable with a dental procedure and that anxiety levels were generally low. 11 Our study has some weaknesses. First, it is a retrospective study based on the experience of a single surgeon operating at a single institution.…”
Section: Discussionmentioning
confidence: 92%
“…Ninety-one percent of their patients felt the pain they experienced during surgery was comparable with a dental procedure and that anxiety levels were generally low. 11 Our study has some weaknesses. First, it is a retrospective study based on the experience of a single surgeon operating at a single institution.…”
Section: Discussionmentioning
confidence: 92%
“…Patients were given the opportunity to state their experiences immediately. Previous literatures investigated patient satisfaction, pain and anxiety level, retrospectively, 7,17 which could be inaccurate as perception may change over time. Our limitation in this study was that a single surgeon was involved in the surgery done and in administering injections.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies focusing on hand procedures have found mean intraoperative pain ratings to be less than 1 out of 10. 15,16 Studies focusing on foot and ankle procedures have reported similar results. 5,6 Although ratings of pain intensity are useful, they are also unidimensional and ultimately provide a limited view of patient pain.…”
Section: Introductionmentioning
confidence: 73%
“…Past studies have found that anxiety during these surgeries is common, but it tends to decline steadily as the perioperative period progresses and patients become more comfortable with the surgical setting. 5,6,16,21…”
Section: Discussionmentioning
confidence: 99%